STUDENTS’ PERCEPTION OF THE USE OF PROBLEM-BASED LEARNING IN ENGLISH LANGUAGE LEARNING IMPLEMENTED BY PROFESSIONAL TEACHERS - Ni'ma, Sita Lailatun; Imaniar, Fahmy; Rachmania, Andriani (FKIP - Universitas Tanjungpura, 2026)
This study investigates how students view the use of Problem-Based Learning (PBL) in learning English, especially when taught by teachers who have followed training. PBL is considered a student centered learning method that can increase motivation, cooperation, and critical thinking skills. But, the success of this method depends not only on the teacher's ability but also on how students experience and view PBL in practice. The purpose of this study is to describe students' views on PBL in English classes and to identify the aspects that are considered positive and negative. This study used a quantitative descriptive method involving 111 students from three high school classes. Data were obtained through a questionnaire consisting of 20 questions, divided into three indicators: student interest, teacher guidance quality, and the impact of training. To analyze the data, descriptive statistical methods were used to calculate the average value of each indicator. Based on the results of the study, it shows that in general students like PBL. The average score ranges from 3.18 to 3.97. The highest aspect is teacher professional development, while the lowest aspect is student preference for PBL. These results indicate that although PBL is effective in increasing participation, critical thinking skills, and teaching quality, there is an additional need to improve students' confidence in communicating and make them more fond of this method. In conclusion, this study emphasizes the importance of teacher training and qualifications in the successful implementation of PBL.